Study guides

☆☆

Q: What is a squared plus b squared equals c squared when a equals 2 and c equals 6?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

89

(x + 3)(x + 2)

(x-3)(x-2)

(-4,-6)

(x - 6)(x - 2)

Related questions

2 squared plus 2 x 3 = 10, 7 squared plus 7 x 2 = 63, 6 squared plus 6 x 5 = 66,8 squared plus 8 x 4 = 96 so 9 squared plus 9 x 7 = 81 + 63 = 144.

x = the square root of -2

89

(x + 3)(x + 2)

(x-3)(x-2)

(-4,-6)

X squared = x+6 6+x=x squared X=6

3(2x - 1)(x - 2)

(x - 6)(x - 2)

i think its 3y squared

This is the common form of the Pythagorean Theorem. It describes the relationship between the two legs of a right triangle and the hypotenuse.

4

People also asked